Conversation analysis as a technique for exploring the dynamics of a mediated interview. - Friedland D; Penn C (International Journal of Language & Communication Disorders)
The study analysed the dynamics of a mediated medico-legal interview using conversation analysis (CA) as a key methodology. The aim of using CA was to identify both facilitators and inhibitors of a successfully mediated interview, using a detailed microscopic analysis of the dynamics involved. A 45-minute interview with the client's parents, the speech pathologist and the interpreter was taperecorded and analysed according to CA principles. Results revealed several facilitators, including equal and active roles, use of code switching, familiarity between the interviewer and interpreter, and use of repetition. Inhibitors included different agendas, complicated repair trajectories and interruptions. In addition, aspects such as cultural brokerage were identified that could be considered neither as facilitators nor as inhibitors. Each area is discussed in detail using extracts from the transcription.